2020
DOI: 10.1021/acs.accounts.9b00636
|View full text |Cite
|
Sign up to set email alerts
|

Trialkylsilyl-Substituted Silole and Germole Dianions as Precursors for Unusual Silicon and Germanium Compounds

Abstract: Conspectus Group 14 element heteroles are the heavier analogues of cyclopentadienes in which a heavier group 14 element atom replaces the sp3 carbon atom. In particular siloles and, to a somewhat smaller degree, germoles attracted considerable attention since the early 1990s due to their favorable photophysical properties which allowed the construction of OLEDs using group 14 element heteroles as emissive or electron-transport layers. Anions and in particular dianions derived from group 14 element heteroles ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 71 publications
(144 reference statements)
0
24
0
3
Order By: Relevance
“…Since West et al reported on the first characterized delocalized germole dianion, [14] considerable progress has been made during the last two decades. Especially the groups of Tilley, [15] Boudjouk [16] and Müller [17] synthesized a variety of germole dianions and discussed their chemistry (compound 5, Scheme 1) The rare number of geminal dianions available and hence the undeniable interest in these derivatives drove our motivation to contribute to this field. Thereby our intention was the design of a reasonable preparative-scale approach for the synthetically highly attractive geminal bisgermenolate.…”
mentioning
confidence: 99%
“…Since West et al reported on the first characterized delocalized germole dianion, [14] considerable progress has been made during the last two decades. Especially the groups of Tilley, [15] Boudjouk [16] and Müller [17] synthesized a variety of germole dianions and discussed their chemistry (compound 5, Scheme 1) The rare number of geminal dianions available and hence the undeniable interest in these derivatives drove our motivation to contribute to this field. Thereby our intention was the design of a reasonable preparative-scale approach for the synthetically highly attractive geminal bisgermenolate.…”
mentioning
confidence: 99%
“…The second mainspring for the development of the chemistry of tetroles was the possible occurrence of aromaticity in the negatively charged ions, II and III , and their applications as ligands in transition metal chemistry [13–16] . During the last years, the group of Saito and the Oldenburg team contributed to this field by demonstrating that tetrole dianions III are suitable precursors for a wide variety of novel compounds with the tetrel element in unusual coordination environments [13,16–19] . In view of the vast existing body of knowledge on tetrole's material chemistry, we asked ourselves if the favorable photophysical properties of tetroles might be combined with magnetic properties resulting from an unpaired spin as for example in tetrolyl radicals IV .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] During the last years, the group of Saito and the Oldenburg team contributed to this field by demonstrating that tetrole dianions III are suitable precursors for a wide variety of novel compounds with the tetrel element in unusual coordination environments. [13,[16][17][18][19] In view of the vast existing body of knowledge on tetrole's material chemistry, we asked ourselves if the favorable photophysical properties of tetroles might be combined with magnetic properties resulting from an unpaired spin as for example in tetrolyl radicals IV. An inspiration came from one report by the West group who communicated on the existence and stability of a silolyl-based biradical V with triplet ground state and its surprisingly low reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 The digermylene isomer X is preferred when the substituent R is a multidentate ligand. [30][31][32][33][34][35][36][37][38][39] Following previous investigations from our laboratory, 40 we probed the potential of salt metathesis of group 14 element dianions XI with group 14 element dihalides XII followed by 1,2elimination for the synthesis of heavy vinylidenes III (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…Following previous investigations from our laboratory, 40 we probed the potential of salt metathesis of group 14 element dianions XI with group 14 element dihalides XII followed by 1,2-elimination for the synthesis of heavy vinylidenes III ( Fig. 3 ).…”
Section: Introductionmentioning
confidence: 99%